High-Resolution MR for Follow-Up of Intracranial Steno-Occlusive Disease Treated by Endovascular Treatment - Wang, Junjie; Zhang, Shun; Lu, Jun; Qi, Peng; Hu, Shen; Yang, Ximeng; Chen, Kunpeng; Wang, Daming (Frontiers in Neurology, 2021)
Background and Purpose: Endovascular recanalization is an alternative option for symptomatic intracranial atherosclerotic steno-occlusive disease (ICAD). Accurate noninvasive alternatives to DSA for follow-up imaging after endovascular treatment are desirable. We wanted to assess the utility of high-resolution magnetic resonance (HR-MR) for this purpose. Materials and Methods: From January 2017 to June 2020, data of 30 patients with 34 intracranial steno-occlusive lesions who underwent endovascular recanalization and received HR-MR follow-up were retrospectively collected in our prospective database. Studies were evaluated for quality of visualization of the vessel lumen, restenosis rate, and accuracy of HR-MR with DSA used as the reference standard. Results: A total of 34 intracranial steno-occlusive lesions in 30 patients, with 28 lesions undergoing balloon angioplasty [including 13 drug-coated balloon (DCB)] and 6 lesions undergoing stenting, were enrolled. The median age was 65.0 years (IQR 56.5-73.3 years); mean imaging follow-up time was 11.4 months (IQR 6.8-15.0 months). Median degree of preprocedural and residual stenosis was 69% (IQR 54.8-94.5%) and 35% (IQR 15.0-50.0%), respectively. Intracranial periprocedural complications occurred in 1 (3.6%) patient. In the case of stainless-steel stent (n=1), there was a signal drop at the level of the vessel, which did not allow to evaluating the vessel lumen. Whereas this was visible in case of nitinol stents (n=6) and angioplasty (n=27). The overall restenosis rate was 23.5% (n=8) [14.3%(1/7) in the stent group versus 25.9%(7/27) in the angioplasty group). The DCB subgroup showed a lower rate of restenosis in comparison with the percutaneous transluminal angioplasty (PTA) subgroup [15.3%(2/13) vs. 35.7%(5/14)]. Conclusion: HR-MR is a reliable noninvasive method for demonstrating the vessel lumen and diagnostic follow-up after endovascular recanalization for ICAD.